KEPUTUSAN PEMBELIAN ONLINE KOPI NUANSA GEMBIRA - Lely Afiati (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to determine the influence of information quality, trust, and convenience on online purchasing decisions on the purchase of Nuansa Gembira coffee in Semarang City. Data by distributing questionnaires using Google Forms with as many as 80 respondents with Convenience sampling techniques. Data analysis using SPSS version 25. The results showed that the quality of information and trust had a positive and significant effect on online purchasing decisions. In contrast, convenience had a positive but insignificant effect on online purchase decisions. Keywords: Online Purchase Decision, Quality of Information, Trust, Convenience